2022
DOI: 10.1007/s13399-022-02445-w
|View full text |Cite
|
Sign up to set email alerts
|

Using a novel continuous bioreactor in enhancing the biogas production

Abstract: Background: Since fossil fuels are limited and their burning is considered the main reason for environmental pollution, thinkers in the energy section are looking for a substitute for them. They have considered biogas as a potent replacement. Constant composition and volumetric rate, are ones of the challenges faced in term of using biogas. Therefore, in this study, a novel easily portable continuous bioreactor was designed and constructed to produce biogas at constant composition and volumetric rate, which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The VS and NS of raw materials are determined by the weight difference method. The loss mass is equal to VS, and the remaining mass is equal to NS [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The VS and NS of raw materials are determined by the weight difference method. The loss mass is equal to VS, and the remaining mass is equal to NS [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to measure TS, a 5 g sample was taken and dried at 105 • C for 12 h. DS was determined knowing that it was equivalent to the humidity reading. For VS determination, the sample was placed in a muffle furnace and heated at a temperature of 550 • C for 1 h. The mass lost is equal to VS and the mass remaining is equal to NS [26,34]. The physical parameters of MA and inoculum are presented in Table 1.…”
Section: Substrate and Inoculummentioning
confidence: 99%
“…In the chamber, the biomass is mixed and heated to a temperature of 20 • C. From AC-II, the substrate is fed to AC-III, where mesophilic conditions are maintained. Studies showed that methanogenesis works efficiently when the AC-III temperature is maintained at 37 • C [32][33][34]. The substrate from AC-III to AC-III does not adversely affect the methanogenic bacterial colonies that exist in AC-III.…”
Section: Description Of Laboratory Standmentioning
confidence: 99%
See 1 more Smart Citation